Narrative exposure therapy for survivors of human trafficking: feasibility randomised controlled trial. Issue 6 (28th November 2021) - Brady, Francesca; Chisholm, Amy; Walsh, Eileen; Ottisova, Livia; Bevilacqua, Leonardo; Mason, Claire; von Werthern, Martha; Cannon, Teresa; Curry, Christina; Komolafe, Kemi; Robert, Rachel Elizabeth; Robjant, Katy; et al.
Abstract : Background: Human trafficking is a grave human rights violation and a major public health concern. Survivors present with high rates of mental health problems including post-traumatic stress disorder (PTSD). Studies of effective treatments for PTSD in survivors of human trafficking are lacking. Narrative exposure therapy (NET) is an effective PTSD treatment for multiple, prolonged and complex trauma, but its efficacy has not been rigorously tested in survivors of human trafficking. Aims: To test the feasibility and acceptability of a randomised controlled trial (RCT) offering NET as a treatment for PTSD in trafficking survivors with a history of multiple traumatic events, as well as providing preliminary evidence regarding its efficacy (trial registration: ISRCTN95136302). Method: A single-blind RCT compared NET with a wait-list control in survivors of trafficking with PTSD ( n = 25). In the NET arm of the study, participants attended a mean of 17 sessions. Results: NET was well tolerated by participants. There were significant reductions in PTSD, depression and anxiety symptoms post-treatment in the NET group but no significant change in the wait-list group. Conclusions: The results indicate that NET is a promising and acceptable treatment for trafficking survivors. Psychological therapy in an RCT design can be safely delivered to this vulnerable group, although modifications are required to ensure their holistic needs are properly addressed.